Pelatihan Manajemen Konten Promosi pada Media Sosial untuk Peningkatan Brand Produk Home-Industry - Purbiyanti, Emi; Ritonga, Utan Sahiro; Yunita; Putri, Nurilla Elysa; Sulastri, Merna Ayu (Jurnal Pengabdian Tri Bhakti, 2024)
The implementation of community service aims to empower community through increased capabilities and independence. By utilizing science and technology, hoped that community can find social, economic, and environmental problem solutions. In digital era, important for stakeholders to provide knowledge about digital platforms use such as social media for marketing. Indonesia with more than 204.7 million internet users, shows great potential utilizing online marketing. Through counselling and training, community can learn to manage promotional content effectively includes Effectiveness of Posting Time, Content Elements, Hashtag Use, Promotional content types, Promotional content planning, Promotional content topics, Copywriting Functions, and Artificial Intelligent (AI) Applications Use in Copywriting. Community service activity which was attended by 25 members of Burai Village Tourism Awareness group with senior high school education as majority levels is potential Human Resource to support village economic development. Evaluation results to participants showed 80% increase in ability to several aspects such as choosing most effective posting time, choosing video content as most responsive content element, efficiency in using number of hashtags, choosing video as most effective promotional content, and scheduled content planning. However, there are still some aspects that need to be improved, especially to selection promotional content topics, understanding copywriting function, and use AI applications to support copywriting, which achieved increase in ability of 50% of total participants. This indicates that there is still need for more intensive training programs in terms of frequency and quality training to improve promotional content management competencies that reach more social media user responses.